Third order NLO properties of modified azo-azulenes - Nizioł, J.; Essaidi, Z.; Sahraoui, Bouchta (Photonics Letters of Poland, 2010)
In this work there are reported third order nonlinear optical properties of some new azo- functionalized azulene derivatives. They were studied using standard methods - degenerate four waves mixing and third harmonic generation and nonlinear optical absorption. The obtained results allow us to conclude that NLO properties of an azulene molecule can be significantly enhanced by substitution with an electron accepting an acetamidophenyl group. Full Text: PDF References R.L. Nelson, F. Kajzar, T. Kaino (eds.), Organic Photonic Materials and Devices XI, Proceedings of SPIE, 2009, ISBN 0819474592. M.G. Kuzyk, C.W. Dirk, Characterization Techniques And Tabulations For Organic Nonlinear Optical Materials (CRC Press 1998), ISBN 0824799682. P.G. Lacroix, I. Malfant, G. Iftime, A.C. Razus, K. Nakatani, J.A.Delaire,"Azo-Azulene Derivatives as Second-Order Nonlinear Optical Chromophores", Chem. Eur. J. 6, 2599 (2000)<a href="http://dx.doi.org/10.1002/1521-3765(20000717)6:14<2599::AID-CHEM2599>3.0.CO;2-G">[CrossRef] O.K. Abdou-Zeid, H.K. Sinha, T.P. Steer,"S2?S0Spectroscopy of Azulene and Its 2-Chloro, 2-Methyl, and 1,3-Dimethyl Derivatives", J. Mol. Spect. 183, 42 (1997)[CrossRef] R. Hermann, B. Pedersen, G. Wagner, J.H. Youn,"Molecules with potential applications for non-linear optics: the combination of ferrocene and azulene", J. Organometallic Chem. 571, 261 (1998)[CrossRef] J.O. Morley,"Nonlinear optical properties of organic molecules. 7. Calculated hyperpolarizabilities of azulenes and sesquifulvalene", J. Am. Chem. Soc. 110, 7660 (1988)[CrossRef] P. Wang, P. Zhu, C. Ye, A.E. Asato, R.S.H. Liu,"Theoretical Investigation and Molecular Design of Some Azulene Derivatives with Large Hyperpolarizabilities", J.Phys.Chem.A, 103, 7076 (1999)[CrossRef] A.E. Asato, R.S.H. Liu, R.V. Pushkara, Y.M. Cai,"Azulene-containing donor-acceptor compounds as second-order nonlinear chromophores", Tetrahedron Lett. 37 419 (1996)[CrossRef] A.C. Razus, L. Birzan, N.M. Surugiu, A.C. Corbu, F. Chiraleu,"Syntheses of azulen-1-yl-benzothiazol-2-yl diazenes", Dyes and Pigments 74, 26 (2007)[CrossRef] Y. Zhao, T. Ikeda, Smart Light-responsive materials (Wiley2009), ISBN978-0-470-17578. R.S. Liu, A.E. Asato,"Tuning the color and excited state properties of the azulenic chromophore: NIR absorbing pigments and materials", J. Photochem. Photobiol. C 4, 179 (2003)[CrossRef] P.N. Prasad, D.J. Williams, Introduction to nonlinear optical effects in molecules and polymers (Wiley 1991), ISBN 0-471-51562-0. I. Fuks-Janczarek, B. Sahraoui, I.V. Kityk, J. Berdowski,"Electronic and nuclear contributions to the third-order optical susceptibility of the C60-TTF dyads", Opt.Comm. 236, 159 (2004)[CrossRef] J.P. Bourdin, P.X. Nguyen, G. Rivoire, J.M. Nunzi,"Polarisation properties of the orientational response in phase conjugation", Nonlinear Opt. 7, 1 (1994). M.G. Kuzyk, C.W. Dirk, Characterization techniques and tabulations for organic nonlinear optical materials (Marcel Dekker 1998), ISBN 0-8247-9968-2. F. Kajzar, J. Messier,"Third-harmonic generation in liquids", Phys. Rev. A 32, 2352 (1985)[CrossRef]